Design of triple-/six-spectral perfect absorber using multiple resonance responses of metallic split-ring resonator. (December 2022) - Wang, Ben-Xin; Xu, Chongyang; Zhou, Haiquan; Duan, Guiyuan; Jiang, Jieying; Zhu, Huaxin
Highlights: Simplified design of multiple-spectral absorber is given and suggested in this paper. Triple-spectral absorption is realized merely using single split-ring resonator (SRR). Six-spectral absorption can be achieved via embedding one more SRR. The forming mechanism of the multiple-spectral absorption is analysed. Combination of LC mode, quadrupole, high-order of SRR results in multiple-spectral absorption. Abstract: Multiple-spectral absorber is a kind of functional device with important applications in optoelectronic technology areas. However, the implementation of multiple-spectral absorber usually requires many metallic elements relying on design methods of stacking or coplanar, leading to complex structure design, time-consuming and laborious fabrication procedures. Simplified design of multiple-spectral absorber is given and suggested in this paper. It is revealed that the triple-spectral absorption is realized by merely using single metallic split-ring resonator (SRR). Combined effect of fundamental mode LC resonance, quadrupole resonance and high-order response of SRR gives rise to the triple-spectral absorption. What is more important is that six-spectral absorption can be achieved via embedding one more SRR on the basis of original SRR. Under the aid of the near-field maps, the formation mechanism of six-spectral absorption is discussed. Compared with previous metamaterial absorbers, the suggested devices have the obvious advantages of simple structure design, low construction cost, and thus can have large potential for applications.